2016
DOI: 10.5624/isd.2016.46.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of condylar positions in patients with temporomandibular disorders: A cone-beam computed tomographic study

Abstract: PurposeThis study was performed to compare the condylar position in patients with temporomandibular joint disorders (TMDs) and a normal group by using cone-beam computed tomography (CBCT).Materials and MethodsIn the TMD group, 25 patients (5 men and 20 women) were randomly selected among the ones suffering from TMD according to the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD). The control group consisted of 25 patients (8 men and 17 women) with normal temporomandibular joints (TMJs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
26
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 26 publications
6
26
0
4
Order By: Relevance
“…9 Imanimoghaddam et al also showed that decreased posterior joint space is a ore prominent finding in TMD patients. 11 Cho and Jung reached a similar conclusion, which is in agreement with the present study. 25 Lelis et al found that there were no significant differences in the condylar positions between the centric relation and the maximum intercuspation in either symptomatic or asymptomatic young adults.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…9 Imanimoghaddam et al also showed that decreased posterior joint space is a ore prominent finding in TMD patients. 11 Cho and Jung reached a similar conclusion, which is in agreement with the present study. 25 Lelis et al found that there were no significant differences in the condylar positions between the centric relation and the maximum intercuspation in either symptomatic or asymptomatic young adults.…”
Section: Discussionsupporting
confidence: 93%
“…A considerable posterior position of the condyle often reveals a disorder. 11 It appears that joints with disk displacement tend to have a posterior condylar position. 12 The TMJ disk is interposed between the posterior slope of the eminence and the functional surface of the condyle to act as a buffer between the 2 bones.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that many etiologic factors, such as parafunctional and postural habits, but also psychological and occlusal factors, are usually attributed to the onset of TMD and also to the perpetuation of the muscular-related disturbances [ 2 ], it is necessary to understand the anatomy and morphology of the Temporomandibular Joint (TMJ) in order not to misinterpret a normal situation as an abnormality [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this hyperactivity a headache or neck pain appears, often misdiagnosed as migraine or tension type headache. Temporomandibular joint pain and muscle myalgia, which are a burden to the patient, are hard to submit to a repeated prosthetic treatment [ 7 9 ]. In the process of prosthetic treatment of edentulous patients, the most important task is establishing the proper intraarticular relation in TMJ.…”
Section: Introductionmentioning
confidence: 99%